Understanding primary care physician perspectives on recommending HPV vaccination and addressing vaccine hesitancy. Issue 7 (3rd July 2021) - Tsui, Jennifer; Vincent, Ashley; Anuforo, Bianca; Btoush, Rula; Crabtree, Benjamin F.
ABSTRACT: HPV vaccination rates have improved in recent years, but remain suboptimal in the United States. Physician recommendation is associated with increased uptake; however, specific strategies used by physicians to recommend the vaccine and address hesitancy are underexplored. We iteratively conducted qualitative in-depth interviews with family medicine and pediatrics/adolescent medicine physicians recruited from four primary care settings (federally qualified health centers and hospital-affiliated practices) within a large academic-hospital system in New Jersey. Interviews aimed to understand factors influencing physician recommendations. Transcripts were analyzed iteratively using a team-based, thematic content analysis approach. All physicians reported strong support for HPV vaccination, intention to recommend for target age groups, and providing factsheets to parents. Many physicians used electronic medical records and/or the state immunization registry for monitoring vaccinations, but few were able to report their own clinic-level rates. The majority said they needed to overcome both hesitancy for at least 10–30% of parents and misinformation from the internet. Most cited having their own children vaccinated for HPV as a first-line strategy for addressing parental hesitancy. Other strategies included using data or professional authority to address safety concerns, linking HPV to cervical cancer, highlighting only needing two doses if vaccinated younger, and normalizing the vaccine. While our findings indicate physicians are knowledgeable about HPV vaccination and recommend it to parents, strategies to overcome parental hesitancy varied. Physician, clinic, and health-system-based strategies need to be adopted to overcome parental hesitancy for HPV vaccination.